MENUSANTARAKAN AL-QURAN: MENGEMBALIKAN KEGEMILANGAN BUDAYA KERUKUNAN ANTAR UMAT BERAGAMA - Lufaefi Lufaefi (Himmah: Jurnal Kajian Islam Kontemporer, 2018)
Diversity is a fact that is often denied by some who do not want to be responsible, so often assumeothers who disagree and not the same as himself as the culprit of mistakes, and he is the mostcorrect among others. They forget the history of the plurality of the country. This has actually hurtthe already grounded culture in the archipelago that this nation was born into a culture of diversity.Unfortunately, the person who is reluctant to take responsibility often makes the verses of the Quranjustify his behavior. Consequently, the Qur’an is often politicized for the benefit of the individual, oreven his group by putting aside the cultural heritage mentioned above. Yet the essence of holyrevelation [al-Quran] always tells us to uphold the truth in diversity culture. The culture ofmulticulturalism is indeed embodied and legalized in the Qur’an. This is in accordance with themission of the Koran itself as a revelation that saalih likulli time wa al-meal that has long confirmedthe legality of difference and diversity.Keywords: al Qur’an, archiphelago, diversity, culture, plurality.